Philosophy of the ancient Maya lords of time - McLeod, Alexus (Studies in Comparative Philosophy and Religion., 2018)
Philosophy of the Ancient Maya is an investigation of some of the central topics of metaphysics in the philosophical thought of the Maya people of Mesoamerica, particularly from the Preclassic through Postclassic periods. It covers the topics of time, change, identity, and truth, through comparative investigation integrating Maya texts, practices, and early Chinese philosophy. Adopting an approach I refer to as the "analogical comparative method", the book offers a possible reconstruction of early Maya metaphysical positions with the help of structurally similar positions from early Chinese philosophy. Philosophy of the Ancient Maya investigates Maya philosophical thought via Classic Period stelae, Postclassic Codices, and Colonial era texts such as the Popol Vuh and the books of Chilam Balam.